Physician Satisfaction in the Managed Care Era - Simonet, Daniel (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2005)
The objective of this article is to shed light on physician satisfaction (primary care physicians and specialists) in the Managed Care context. Most surveys to date have brought in mixed results. The article reviews the physician’s perception of cost-control mechanisms, autonomy, and the expression of physician discontent in this new era.